Systematic competence management in the company : consequences for the participation of low-skilled employees in continuing vocational education and training - Schlieker, Mortimer [Verfasser]; Dietzen, Agnes [Verfasser] (My University, 2025)
This article examines the prevalence of systematic competence management in German companies and investigates whether it influences the participation of low-skilled employees in non-formal continuing vocational education and training (CVET). Analyses of the BIBB Training Panel show that highly systematised forms of competence management are established in around a quarter of large companies and that these contribute to an increase in employees’ participation in CVET, whereby highly systematised competence management has a more positive effect for high-skilled employees. (BIBB-Doku)
Keywords: S 1.5 Weiterbildung; P 2.2 An- und Ungelernte; 370; Betriebliche Weiterbildung; Geringqualifizierter; Kompetenzfeststellung; Weiterbildungsbeteiligung; BIBB-Qualifizierungspanel; Kompetenzmanagement